The world of Sholom Aleichem. - Samuel, Maurice, 1895-1972; Dwiggins, W. A. (William Addison), 1880-1956; Plimpton Press; Alfred A. Knopf, Inc. (NY, Knopf, 1952)
"In this book Maurice Samuel tells of a pilgrimage through Sholom Aleichem's world, visiting the townlets and villages of the famous Pale of Settlement, recouting the adventures of the chief characters in the works of Sholom Aleichem, and recreating the folklore, the outlook, and the memories that were in part transplanted to America. To Jews and non-Jews the book is a remarkable revelation of a great man and an extraordinary civilization, now all but extinct." - Dust jacket
Of certain grandfathers -- Man in a forest -- Tevyeh the Dairyman -- The townlet of the tiny folk -- The eternal house -- Love of life -- Faith -- One man to be envied -- Sabbaths and festivals -- From Passover to Passover -- Kasrielevky on a binge -- A tale of two cities -- The judgments of Reb Yozifel -- A seat by the Eastern Wall -- Kasrielevky on Kasrielevky -- Old and new Kasrielevky -- The reconciliation -- A special kind of anti-semite -- Kasrielevky in dissolution -- The sons-in-law of Tevyeh -- The humour of Kasrielevky -- The language of Kasrielevky -- Kasrielevky Billingsgate -- The superstitions of Kasrielevky -- Rabbis and rabbis -- The two extremes -- The open world -- Fringe types -- The children's world -- The cheder -- Aurora Americana -- Death in exile.
Mode of access: Internet.
Keywords: Sholem Aleichem, -- 1859-1916; Jews -- Social life and customs; Jewish literature; Authors, Yiddish; Dust jackets (Binding)